Internationalism after Internationalism: Response to Aarthi Vadde, Chimeras of Form. (7th January 2019) - Hart, Matthew
Abstract : Matthew Hart is an associate professor of English and comparative literature at Columbia University. He is the author of Nations of Nothing but Poetry (Oxford University Press, 2010) and Extraterritorial: A Political Geography of Contemporary Fiction (forthcoming from Columbia University Press). A founding co-editor of the Columbia University Press book series Literature Now, Matt is a former president of A.S.A.P.: Association for the Study of the Arts of the Present and currently vice president of the Modernist Studies Association.